Analysis of Hedonic Test and Total Microbial Plate Numbers on Fish Siomay in Sorong City West Papua - Sukmawati Sukmawati (UNIVERSITAS NEGERI PADANG, 2020)
One of the Indonesian snacks that can be found in all regions is fish siomay. fish siomay in the city of Sorong, there have been no reports on both the level of community preference and food security. The purpose of this study was to determine the level of community preference and the total number of microbial plate numbers snacks on fish siomay in the city of Sorong, West Papua. The method used in this research is descriptive method and experimental method. The results showed that for the hedonic test had a varying degree of preference for each sample, while the total number of plates did not exceed the maximum limit, then for the correlation of the two tests showed there was a relationship. The hedonic test results from the five samples show the best level of preference is the BS sample, and the EH sample, then the AQ sample, and the DS sample and the lowest preference level is the CR sample. While the sample of fish siomay scattered in the city of Sorong was suitable for consumption.